Dawr al-mar’ah fī usrat al-salafīyah al-jihādīyah fī farḍ al-inḍibāṭ ‘alá jism al-abnā’ - Fikriyati, Umi Najikhah; Azca, Muhamad Najib (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
In a radical group, women have strategic and significant roles as a martyr, creating some kindship genealogies, recruiting members, and reproducing religious values for their family members. This paper intends to study more deeply about women’s role in reproducing religious values in the Salafi Jihadi’s family, specifically in the terrorism convicted family. When their husbands are jailed because of terrorism cases, the terrorists’ wives will become the family’s center. Besides as a mother, they also must replace their husband’s role such as giving livelihood and reproducing religious values for their children. In this study, reproduction of religious values in the Sisi and Susi’s family (unreal names) is implemented through child’s body disciplines. It undertakes through some activities such as (1) space concept (2) activity and behavior (3) punishment.